Uji Diagnosis NS1, IgG dan IgM Dengue Metode Immunokromatografi dan Elisa - Kesuma, Suryanata (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Dengue fever is a disease caused by the dengue virus (DENV). Detection of NS1 antigen can be useful for early confirmation of DENV infection. NS1 antigen can be detected from the first day of illness and lasts up to 9-10 days. Other supporting examinations are dengue virus IgG and IgM examinations. The purpose of this study was to review the sensitivity and specificity of the dengue virus NS1, IgG, and IgM tests through literature testing. This type of research is descriptive. The literature used is scientific journals which are the top journals searched using the google search engine and contains complete information and data related to the sensitivity and specificity of NS1, IgG, and IgM Dengue Virus examinations. Based on the review, it was found that the sensitivity of the NS1 antigen in the Rapid Immunochromatographic method was in the range of 48%-92% and specificity was 73%-100%, in the ELISA method the sensitivity range was 42%-84% and specificity was 89%-99%. In the examination of IgG and IgM antibodies using the Rapid Immunochromatography method, the sensitivity ranges from 6%-73% and specificity 36%-100%. Examination of IgG and IgM antibodies using the ELISA method obtained sensitivity in the range of 6%-58% and specificity 56%-100%. The results of the review conducted showed that the sensitivity of the NS1, IgG, and IgM tests for Dengue Virus with the Rapid Immunochromatography method was better than the ELISA method, but the specificity for the NS1, IgG, and IgM tests for Dengue Virus ELISA method was better than the Rapid Immunochromatography method. In addition, the Rapid Immunochromatography method of NS1 antigen examination showed higher accuracy than IgG and IgM antibodies in screening for dengue virus infection.